KiwiChat camp : experiences and perceptions of children with complex communication needs and their family/whānau : a thesis presented in partial fulfilment of the requirements for the degree of Master of Speech-Language Therapy at Massey University, Albany, New Zealand - Bell, Jessamy Lauren (Massey University, 2018)
Children with complex communication needs (CCN) who use augmentative and alternative communication (AAC) require a significant amount of intervention to achieve communicative competence. This study explored the perceptions and experiences of 16 children with CCN and their families who attended KiwiChat Camp, an intensive 5-day camp focused on using AAC in everyday contexts. Very few studies have explored the perceptions and experiences of camp interventions. KiwiChat camp involved explicit training sessions for parents and small group intervention for children who use AAC. All of the family members (parents, siblings and children who use AAC) were immersed in aided language stimulation throughout the day. They interacted with other families of children who use AAC and older AAC mentors. Pre-and-post data were collected through camp surveys for parents and children who use AAC and semistructured interviews with parents and siblings. The quantitative data were analysed using descriptive statistics, while the qualitative data were analysed using a general inductive approach. The results indicated that families enjoyed the camp experience and parents experienced increased motivation, inspiration and empowerment following camp. However some felt overwhelmed during camp. They also perceived an increase in a range of communication outcomes (increased AAC use, confidence and knowledge) and sociocultural outcomes (connections with others who use AAC, a sense of belonging and development of identity). Recommendations for future camps and research studies are outlined.
Keywords: Children with disabilities -- New Zealand -- Means of communication; Children with disabilities -- New Zealand -- Family relationships; Parents of children with disabilities -- New Zealand -- Attitudes; Communicative disorders in children -- New Zealand -- Study and teaching; Outdoor education -- New Zealand -- Study and teaching